The Research Progress of PD-1/PD-L1 Inhibitors Enhancing Radiotherapy Efficacy - Wen, Lu; Tong, Fan; Zhang, Ruiguang; Chen, Lingjuan; Huang, Yu; Dong, Xiaorong (Frontiers in Oncology, 2021)
Approximately 60%–70% of patients with malignant tumours require radiotherapy. The clinical application of immune checkpoint inhibitors (ICIs), such as anti-PD-1/PD-L1, has revolutionized cancer treatment and greatly improved the outcome of a variety of cancers by boosting host immunity.However, radiotherapy is a double-edged sword for PD-1/PD-L immunotherapy. Research on how to improve radiotherapy efficacy using PD-1/PD-L1 inhibitor is gaining momentum. Various studies have reported the survival benefits of the combined application of radiotherapy and PD-1/PD-L1 inhibitor. To fully exerts the immune activation effect of radiotherapy, while avoiding the immunosuppressive effect of radiotherapy as much as possible, the dose selection, segmentation mode, treatment timing and the number of treatment sites of radiotherapy play a role. Therefore, we aim to review the effect of radiotherapy combined with anti-PD-1/PD-L1 on the immune system and its optimization.